Neurocysticercosis in Ecuador: Spatial clustering, social determinants, and epidemiological trends (2017-2023). - Andrés Fernando Vinueza-Veloz; Marlon Fabricio Calispa-Aguilar; Pamela Vinueza-Veloz; Tannia Valeria Carpio-Arias; Jefferson Santiago Piedra-Andrade; María Fernanda Vinueza-Veloz; Belkys Galindo-Santana (PLoS Neglected Tropical Diseases)
Background Neurocysticercosis (NCC) is endemic in Ecuador. This study analyzes spatial clustering of municipalities with high and low incidence rates (hot and cold spots) and its association with social determinants of health (SDH). Methods This ecological study used national anonymized hospitalization records (2017-2023) and outpatient registries (2021), as well as municipality-level SDH data. Data were aggregated at the municipality level. Spatial clustering was assessed using Local Indicators of Spatial Association (LISA). SDH were compared between hot and cold spots using parametric and non-parametric tests. Results Between 2017 and 2023, 735 NCC cases were recorded. Annual incidence decreased from 1.01 to 0.44 per 100,000 inhabitants-year between 2017 and 2023. There was no difference in NCC incidence rates between males and females. Spatial analysis revealed clustering of municipalities with high NCC incidence rates in southern Ecuador (Moran's Index = 0.46, p < 0.001). In comparison with cold spots, hot spots exhibited higher income inequality (Gini index: 0.48 vs. 0.46; p < 0.001), higher density of Creole pigs (6,672.84 vs. 724.73 per 100,000 inhabitants; p = 0.010), but lower population density (28.00 vs. 117.20 inhabitants/km²; p < 0.001), rainfall (1,183.90 vs. 2,126.93 mm³/m²; p < 0.001), and temperature (18.47°C vs. 23.98°C; p < 0.001). Paradoxically, hot spots had higher sewerage coverage (77.00% vs. 50.70%; p = 0.010) and physician density (220.95 vs. 138.69 per 100,000; p = 0.010). Conclusions NCC hot spots were identified in southern Ecuador, which included rural, arid and cooler municipalities reliant on traditional pig-rearing and where income distribution was more unequal. Despite available sanitary infrastructure and healthcare access, structural inequalities seem to undermine NCC control efforts in endemic regions. To disrupt NCC persistence, government strategies must prioritize systemic reforms addressing income gaps alongside targeted public health interventions.